Today was not a good day: offender accounts of the incidents that led to their admission to drug court - Griffin, O. Hayden (Criminal justice studies, 2018)
One method that has been touted to help end mass incarceration is using intermediate sanctions. While intermediate sanctions often present as attractive options, there is evidence that as practiced, these sanctions often result in net widening. One of the most common forms of intermediate sanctions are drug courts, which are often viewed as progressive alternatives to locking up people with substance abuse problems. However, along with the dangers of net widening, scholars have shown that many people admitted to drug courts do not seem to have substance abuse problems and could benefit from lesser criminal justice interventions. In the current study, we analyzed intake data from a drug court to determine: (1) what charge(s) drug participants had and (2) how they became involved with the criminal justice system. Among important findings were that a large number of drug court participants were arrested for the possession of one drug only (often marijuana) and that more than half of participants came to the attention of the criminal justice system through a traffic stop rather than through repeated encounters with the criminal justice system.